Effect of distributed generation placement to load noise on the KH-01 feeder at PT. PLN (PERSERO) ULP Krueng Geukueh - Azizi, Muhammad; Meliala, Selamat (Geuthèë Institute, 2024)
Distributed Generation is a power plant with a small capacity which is usually located close to the load in the electric power distribution system. One effort to reduce the value of power losses and also improve voltage drops in the distribution network is by interconnecting DG in the electric power distribution system. This research method uses data from PT. PLN (Persero) ULP Krueng Geukueh, the data was processed and simulated using ETAP 12.6 software with several scenarios carried out. The results obtained before connecting distributed generation, the resulting power losses were 97 MW for active power losses and 114 Mvar for reactive power losses. and after the introduction of distributed generation using scenario 1, it was able to improve the value of power losses by 94 MW for active power losses and 107 Mvar for reactive power losses and scenario 2 was able to reduce power losses by 71 MW for active power losses and 57 Mvar for reactive power loss and by using scenario 3 the resulting power loss value increases by 139 MW for active power loss and 147 Mvar for reactive power loss. It can be concluded that scenario 2 is able to improve the voltage profile and power losses on the KH-01 feeder.